Construction and Expression of Immunotoxin Anti EGFRvIII scFv-HPR Conjugate in Pichia pastoris as A Targeted Drug Candidate for Cancer Therapy - Yuliawati Yuliawati; Retno Damayanti Soejoedono; Asrul Muhamad Fuad (ANNALES BOGORIENSES, 2014)
Epidermal growth factor receptor variant III (EGFRvIII) is a mutant of EGFR lacking 267 amino acids (exon-2 through 7) within its extracellular domain, resulting in the formation of a new epitope as a tumorspecific target. EGFRvIII is commonly found in GBM, breast, ovarian, prostate, and lung carcinomas. Antibodies or part of antibodies (e.g. single chain variable fragment or scFv) with specific activity against this receptor have been developed. These antibodies are internalized into the cell after receptor binding. Ribonucleases can be cytotoxic due to their inherent ability to degrade RNA, therefore causing cell death via inhibition of protein synthesis. The aim of this research is to construct, clone and express an immunotoxin-based conjugate combining an anti-EGFRvIII scFv with a HPRmut (human pancreatic ribonuclease mutant variant) in Pichia pastoris. The anti-EGFRvIII scFv gene was cloned into yeast expression vector pPICZαA and fused with EGFP gene as a marker. The HPRmut gene was subsequently cloned at the C-terminal of the scFv::EGFP fusion, resulting in the scFv::EGFP::HPR fusion construct. The fusion construct was successfully obtained and nucleotide sequence of plasmid was verified. This construct was used to transform Pichia pastoris SMD 1168H. The gene fusion was successfully transformed and expressed in P. pastoris with a transformation efficiency of 102 cfu/μg DNA. The transformed yeasts were screened on agar media containing up to 1000 μg/ml zeocin. Yeast transformants showed green fluorescent due to the expression of EGFP gene. The recombinant proteins have been expressed and secreted from P. pastoris as showed by immunoblotting and SDS-PAGE analyses, then purified by affinity chromatography method. The selected yeast transformant produced at least 15.85 mg of purified protein per liter of yeast culture.